DISCUSSION ON COMPOUNDING METHOD AND EMPIRICAL METHOD APPLYING ON CALCULATING THE STRESS INTENSITY FACTOR IN MSD - WU WenLong; MAO KeYi; GONG TianChen; YANG YaNing (Jixie qiangdu)
Principle of compounding method and empirical method was compared and analysised. Based on the three boundary condition decomposition methods of structure with multiple site damage（ MSD）,stress intensity factor（ SIF） of MSD crack tips was calculated with compounding method and empirical method respectively,and compared with the result of FRANC2 D Simulation. Finally a more accurate calculation method of stress intensity factor of MSD cracks was raised.